If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-3(x+2)=-7+2(x-3)
We move all terms to the left:
5x-3(x+2)-(-7+2(x-3))=0
We multiply parentheses
5x-3x-(-7+2(x-3))-6=0
We calculate terms in parentheses: -(-7+2(x-3)), so:We add all the numbers together, and all the variables
-7+2(x-3)
determiningTheFunctionDomain 2(x-3)-7
We multiply parentheses
2x-6-7
We add all the numbers together, and all the variables
2x-13
Back to the equation:
-(2x-13)
2x-(2x-13)-6=0
We get rid of parentheses
2x-2x+13-6=0
We add all the numbers together, and all the variables
7!=0
There is no solution for this equation
| x+3(-19/11)=-6 | | 1/2x+8-6=4 | | 11x+15=5x-19 | | -(8+3x)+5=2x+5 | | .30x+140=x | | 3(x+2)+9=42 | | -10k−6=9−7k−8k | | -(8+3x)+5=2x | | 41-21x+12x=44 | | 3y+9=9 | | 3(7x-5)+3(6-4x)-4(2x+4)=-4 | | 36(-3)+x-55=-156 | | 2n-4=6+4n | | 5(x)+24-65=79 | | -4=6+2n | | 6(-3v+1)=5(-22 | | 2(5x-3)-(2x-4)=5-(6x=1) | | 66=3u+15 | | -0.4n=3.2 | | (15x+3)=108° | | -12=-48v | | 9x-40=8x+40 | | 7p+8=5p+4p | | 3(5+c)=2(c-5 | | 10=2u-16 | | r-26=-46 | | 2(4Z-11)=3(3z+11)-z | | 8p+4p=12 | | -2(z-8)=1/4(12z+4) | | -1/2=-3/5y+4/5 | | 7p-5=9p+8 | | 1+2x3+4x5=65 |